2011
DOI: 10.1371/journal.pone.0021362
|View full text |Cite
|
Sign up to set email alerts
|

Bocavirus Episome in Infected Human Tissue Contains Non-Identical Termini

Abstract: Human bocaviruses (HBoV) are highly prevalent human infections whose pathogenic potential remains unknown. Recent identification of the first non-human primate bocavirus [1] in captive gorillas raised the possibility of the persistent nature of bocavirus infection. To characterize bocavirus infection in humans, we tested intestinal biopsies from 22 children with gastrointestinal disease for the presence of HBoV DNA. Four HBoV-positive tissue samples were analyzed to determine whether viral DNA was present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 45 publications
4
97
2
Order By: Relevance
“…Previous studies revealed a remarkable feature of the 3= NCR of primate bocaparvoviruses: those of HBoV1, HBoV2, and HBoV3 fold into almost identical secondary structures (45,46). This feature appears to be unique; it is not shared by the carnivore bocaparvovirus 1 minute virus of canines (MVC) (23), bocaparvoviruses from other nonprimate species, or other parvoviruses.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies revealed a remarkable feature of the 3= NCR of primate bocaparvoviruses: those of HBoV1, HBoV2, and HBoV3 fold into almost identical secondary structures (45,46). This feature appears to be unique; it is not shared by the carnivore bocaparvovirus 1 minute virus of canines (MVC) (23), bocaparvoviruses from other nonprimate species, or other parvoviruses.…”
Section: Discussionmentioning
confidence: 98%
“…SM protein of EBV during the lytic cycle inhibits protein kinase R activation, whereas EBV LMP-1 protein can prime EBV latency cells for IFN production to establish the viral latency (55)(56)(57). Recent studies have demonstrated that HBoV can establish persistent infection in host cells by forming episomes (58). Persistent HBoV infection of polarized HAE cells has also been reported (59).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that feline bocaviruses (51), minute virus of canines (51), porcine bocaviruses (52), and canine bocavirus (53) are genetically distinct from other related bocaviruses, including bocaviruses infecting primates. In addition, differences in splicing (54), length of nonstructural proteins (54), and replication strategies (55) have been documented between bocaviruses infecting primates and bocaviruses infecting other animals. Differences in genome organization and the lack of evidence supporting common ancestry and between bocaviruses infecting primates and those infecting other animals could potentially explain the differences in the relative abundance of CpG dinucleotides between these viruses.…”
Section: Fig 5 Role Of Cpg Depletion In Parvovirus Evolution (A) Commentioning
confidence: 99%